PENGARUH KECANDUAN GAME ONLINE TERHADAP PERILAKU REMAJA DI MABES GAME CENTER JALAN HR.SUBRANTAS KECAMATAN TAMPAN PEKANBARU - Mimi Ulfa; Risdayati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The purpose of this study was to determine the effect of online games on the behavior of students at Police Game Center Street Subrantas Handsome District of Pekanbaru, and the response of parents to the child's behavior. The method used in this research is quantitative descriptive, where the population is taken that students who love to play games online games center at headquarters. To determine the population of researchers using accidental sampling and deployment techniques kesioner with interviews and documentation. Online gaming is providing features 'online community', making online games as a social activity, so it will have an effect on behavior. The gamer will have to play addiction behavior which will certainly have a negative impact. From the analysis done by the results of hypothesis testing t value ≥ t table, atau4032.276 ≥0.195, then the hypothesis is accepted it means there is the influence of online gaming addiction (X) to the behavior of adolescents (Y).Keywords: Game Online, Gamers Behavior, Addictive Games.